ANALISIS PERBEDAAN TINGKAT HARGA PASAR SAHAM, RETURN SAHAM, DAN VOLUME PERDAGANGAN SAHAM PERUSAHAAN SEBELUM DAN SESUDAH STOCK SPLIT - Irwansyah, Muhammad Ajib; Saryadi, Saryadi; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2014)
Stock split is a corporate activity that has no economic value. But many companies do a stock split with the goal set back so that the stock price in the range of more liquid and provide a good signal to investors. This study aims to determine whether there are differences in the level of stock market prices, stock returns and trading volume before and after the company's stock split.Based on the results of the study indicate that there is no difference in the price level of the stock market before and after the stock , no difference in stock returns before and after the stock split, but there is a difference in the company's stock trading volume before and after the stock split.